1986
DOI: 10.1093/geronj/41.3.385
|View full text |Cite
|
Sign up to set email alerts
|

Memory Changes in the Benton Visual Retention Test Between Ages 70 and 75

Abstract: The influences of education and activity on memory of Japanese older adults were investigated. The Benton Visual Retention Test was given to 302 individuals (145 men and 157 women) aged 69 to 71 (average age 70) living in a suburb of Tokyo. Participants were retested 5 years later (average age 75). Memory as evaluated by Benton correct scores declined in both men and women during the 5 years. The influence of the first time Benton score, education, activity, and sex on the second-time Benton score was analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

1990
1990
2006
2006

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 0 publications
2
29
0
1
Order By: Relevance
“…In this study, bivariate association between level of education is quite strong, but when the variable is included with other predictors in multivariate models, the effect of education level on cognitive change becomes insigni® cant. Previous studies have indicated that education has been the most consistent predictor of change in cognitive performance (Albert et al, 1995;Farmer, et al, 1995;Schaie, 1990;Shichita et al, 1986). This discrepancy could be due to the differences in the populations studied, as the number of years of education of the older adults in the current cohort is quite small (mean is about three years).…”
Section: Discussionmentioning
confidence: 70%
“…In this study, bivariate association between level of education is quite strong, but when the variable is included with other predictors in multivariate models, the effect of education level on cognitive change becomes insigni® cant. Previous studies have indicated that education has been the most consistent predictor of change in cognitive performance (Albert et al, 1995;Farmer, et al, 1995;Schaie, 1990;Shichita et al, 1986). This discrepancy could be due to the differences in the populations studied, as the number of years of education of the older adults in the current cohort is quite small (mean is about three years).…”
Section: Discussionmentioning
confidence: 70%
“…Thirteen studies have examined the relationship between education and longitudinal cognitive decline (Shichita et al 1986;Colsher & Wallace, 1991;Evans et al 1993 ;White et al 1994 ;Albert et al 1995;Farmer et al 1995 ;Butler et al 1996 ;Carmelli et al 1997 ;JacqminGadda et al 1997;Arkbuckle et al 1998 ;Lyketsos et al 1999;Christensen et al 2001).…”
Section: Effect Of Educationmentioning
confidence: 99%
“…Table 1 shows 14 studies reporting data on the effect of education on cognitive change that met the inclusion criteria. They may be categorized into four outcomes, including studies reporting the rate of decline being less rapid for the more educated [8,[30][31][32][33], studies failing to find an effect of education on cognitive change [34,35], studies where the effect was restricted to a subgroup or subgroups (women or age subgroups) [36][37][38][39] and studies that were restricted to types of outcome measures [29,[40][41][42][43]. Table 2 shows that the outcomes of these studies appear to be related to the type of cognitive test included in the study.…”
Section: Education As a Predictor Of Cognitive Declinementioning
confidence: 99%
“…One study finding no association between education and cognitive change used a continuous measure [34] and one used categorical measures comprising 7 categories [35]. Five studies [30,32,33,36,39] using categorical measures of education found significant effects, 6 studies [29,31,37,38,42] using a continuous measure of education found significant effects and 1 study [43] using both categorical and continuous measures found significant effects on cognitive change. Both studies finding no effect of education used samples that were relatively homogeneous and comprised of participants with high levels of education, so it is possible that the lack of an effect in these studies was due to restriction of the range in the education variable, or that education is more predictive among samples with lower levels of education than samples with higher levels of education.…”
Section: Education As a Predictor Of Cognitive Declinementioning
confidence: 99%